Optimal sizing and positioning of grid integrated distributed generator: a review - De, Arpita (International Journal of Engineering and Technology, 2020)
The ever-growing population and globalization have resulted into an increase in demand for power. Additionally, ecological concerns like an unnatural weather change have constrained us to locate new and different substitutes to the current conventional sources of energy. To provide a solution to this crisis of energy in a way that is environment friendly, we have focused our attention towards making renewable energy resources as an alternative to currently employed sources of power. This paper contains extensive study on different Distributed Generation (DG) sources, comparing their merits and demerits also comprising of the impact when added to an already existing AC power grid. Accordingly, the planning methodologies have been discussed which will help us in determining which type of DG suits best to our requirement. This paper also contains the review of optimal placement techniques and sizing methodologies for DG system in grid networks, which are together known as Hybrid Energy Systems (HES).Â